Treatment of acute cholecystitis after cardiovascular surgery. (16th October 2019) - Ueno, Kimihiko; Ajiki, Tetsuo; Tsugawa, Daisuke; Akita, Masayuki; Hashimoto, Yu; Terai, Sachio; Tanaka, Motofumi; Toyama, Hirochika; Kido, Masahiro; Fukumoto, Takumi
Abstract: Background: Acute cholecystitis (AC) after cardiovascular surgery (CS) tends to have a serious postoperative course; however, there are few reports of AC after CS. In this study, we investigated the clinical features of AC after CS. Method: Of 26 patients who underwent surgery for AC after CS between 2001 and 2018 were investigated. Of these patients, the severity of AC, onset time, surgical outcomes, and postoperative pathological findings were evaluated. Results: Grade III accounted for 46% (12/26) of the AC after CS patients. Gallbladder drainage did not produce sufficient outcomes in all CS cases. The postoperative hospital days of AC after CS were extended (31/21 days, P = 0.07) and the postoperative pathologic findings revealed a higher rate of gangrenous cholecystitis (88/41%, P < 0.01) than the control group. With regard to the incidence of postoperative complications, there were no differences between CS and the control group (23/24%). The mortality rate of AC after CS was 12%. Conclusion: Because more than 80% of CS cases involved pathologically gangrenous cholecystitis, it may be necessary to perform early surgery for AC after CS, even when the severity of AC is Grade III. Abstract : Highlight To demonstrate the validity of early surgery for Grade III acute cholecystitis after cardiovascular surgery, Ueno and colleagues evaluated gallbladder pathology and surgical outcomes. Since the rate of gangrenous cholecystitis exceeded 80% in acute cholecystitis after cardiovascular surgery, early surgery may be required, despite mortality being 25% in Grade III.